Союз Советских Социалистических Республик - Вавилов Сергей Иванович (1947)
Экземпляры: КХ (20121025) / Инвентарный номер: д72946 / Цена: 50.00 / Сис.шифр: 92 / Авт.знак: Б 79 / ГРНТИ: 13.41 / ББК: 92.0